2020
DOI: 10.1038/s41467-020-14790-3
|View full text |Cite|
|
Sign up to set email alerts
|

Structure of the human cation–chloride cotransporter NKCC1 determined by single-particle electron cryo-microscopy

Abstract: The secondary active cation-chloride cotransporters (CCCs) utilize the existing Na + and/or K + gradients to move Cl − into or out of cells. NKCC1 is an intensively studied member of the CCC family and plays fundamental roles in regulating trans-epithelial ion movement, cell volume, chloride homeostasis and neuronal excitability. Here, we report a cryo-EM structure of human NKCC1 captured in a partially loaded, inward-open state. NKCC1 assembles into a dimer, with the first ten transmembrane (TM) helices harbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
98
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(103 citation statements)
references
References 70 publications
5
98
0
Order By: Relevance
“…The observation of cell-type specific action of these agents is in line with different reversal potentials in mature neuronal populations [115] and calls for comprehensive neuron subtype-specific phospho analysis. The recently reported structural data of CCCs [116][117][118][119] finally lay the foundation to analyze jointly the physiological role of phosphorylation and underlying structural changes to obtain an integrative and mechanistic view of the action of phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…The observation of cell-type specific action of these agents is in line with different reversal potentials in mature neuronal populations [115] and calls for comprehensive neuron subtype-specific phospho analysis. The recently reported structural data of CCCs [116][117][118][119] finally lay the foundation to analyze jointly the physiological role of phosphorylation and underlying structural changes to obtain an integrative and mechanistic view of the action of phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 SLC12A2 encodes for the protein NKCC1 which regulates transport of chloride, potassium and sodium across cell membranes, and is key in modulating ion movement across the epithelium, chloride homeostasis, volume of cells, macrophage activation, and anti-microbial activity. 23,24 Through access to published gene expression studies we observed that across several independent studies, the minor allele (T) of the lead SNP in LINC01184/SLC12A2, rs3749748, was particularly associated with reduced gene expression of SLC12A2 and LINC01184 in monocytes and macrophages. Macrophages are the most abundant resident immune cell type in the skin, and are critical for the resistance against invading microbes and tissue repair.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these traits are linked to cell-volume regulation, which is a key role of NKCC1. 23 While it is unclear whether any of these traits may themselves be causally linked to SSTI susceptibility, cell-volume regulation may be. By changing the intracellular volume of cells, mechanical barrier function may be regulated and affect immune cell and bacterial migration.…”
Section: Discussionmentioning
confidence: 99%
“…The number and position of phospho-sites vary between different family members as they are not evolutionary conserved among isoforms and paralogs [23]. Phosphatases such as protein phosphatase 1 (PP1) counterbalance the act of the kinases [28].…”
Section: Functional Regulation Of the Cation Chloride Cotransporter Fmentioning
confidence: 99%